Observational Evidence and Open Questions on the Role of Internal Tidal Waves on the Concentration and Transport of Floating Plastic Debris - Shanks, Alan L. (Frontiers in Marine Science, 2021)
Tidal currents flowing over benthic relief (e.g., banks, shelf break) produce large internal waves. These waves propagate away from their origin and are capable of crossing the continental shelf and traveling hundreds of kilometers in across seas. Research into the role these internal waves play in the shoreward transport of larval invertebrates and fish unintentionally tested whether they can capture, concentrate and transport floating plastic. Plastic surface drifters deployed in front of sets of internal wave convergences were often captured (>90% captured) and transported kilometers by the waves. While convergence zones over tidally generated internal waves have been demonstrated to capture, concentrate, and transport a variety of larvae and plastic surface drifters there are no investigations into how internal tidal waves may affect the fate and distribution of floating plastic waste. A number of areas of future research are suggested: 1) How much floating plastic is found in internal wave convergences? 2) At locations where internal waves cross the continental shelf, how far offshore does transport commence? 3) How does this vary between geographic locations. 4) How buoyant must floating plastic be to be captured by internal waves? 5) Does capture, concentration and transport of floating plastic vary over the spring/neap tidal cycle? 6) Do seasonal changes in the depth of the pycnocline alter the transport of floating plastic by internal waves? 7) Where the topography of the continental shelf is conducive to the formation of internal waves is more plastic debris transported to shore? 8) In locations where internal waves propagate over large distances, do they capture, concentrate and transport large amounts of floating plastic?